2015
DOI: 10.1097/tp.0000000000000593
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Liver Transplant Candidates

Abstract: In ESLD patient referred for liver transplant, diminished QoL appears to be significantly negatively associated with frailty and not with severity of liver disease as measured MELD. With further study, if frailty is shown to be a remediable condition, targeted programs may help decrease frailty and improve quality of life in ESLD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…2 Frailty and decreased 6-minute walking distance are associated with death and diminished quality of life in liver transplant candidates. 35 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Frailty and decreased 6-minute walking distance are associated with death and diminished quality of life in liver transplant candidates. 35 …”
Section: Introductionmentioning
confidence: 99%
“…To address this question, we examined the United Network for Organ Sharing (UNOS) database, which contains information on all patients listed for liver transplantation in the US. Compared to prior studies of frailty, which were all single-center, 25 the UNOS database offers the advantages of (1) a large population-wide analysis from multiple centers and (2) the use of KPS data collected as part of routine clinical care, allowing for improved generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…Frailty could play a role in a “blended principle model” [ 1 ] of organ allocation, as it is able to assess patients’ overall health status and at the same time potential to be a predictor of both mortality and quality of life [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Derck et al [ 23 ], recently showed that frailty phenotype outperformed MELD in predicting quality of life in the pre-transplant period.…”
Section: Introductionmentioning
confidence: 99%
“…Research on ESLD has focused primarily on patients who are liver transplant candidates Stewart, Hart, Gibson, & Fisher, 2014) and pre-and post-transplantation (Garcia-Rodriguez et al, 2015; Kalaitzakis et al, 2012). Patients awaiting transplantation experience marked worsening of overall health (Lai et al, 2015), physical symptoms like fatigue, affective symptoms like depression and anxiety (Stewart et al, 2014), uncertainty (Kimbell, Boyd, Kendall, Iredale, & Murray, 2015) poor QOL, fear of dying (Bjork & Naden, 2008;Derck et al, 2015), and worsening ascites and confusion due to hepatic encephalopathy (Onyekwere, Ogbera, & Hameed, 2011). Adults with ESLD toward the end of life experience pain (Hansen, Leo, Chang, Zucker, & Sasaki, 2014), symptom distress (Hansen et al, 2015), dyspnea, and depression (Poonja et al, 2014).…”
Section: Physical and Psychological Symptoms In Patients With Esldmentioning
confidence: 99%